Inter-examiner reliability of the Doha agreement meeting classification system of groin pain in male athletes - Heijboer, W. P. M.; Weir, A.; Vuckovic, Z.; Fullam, K.; Tol, J. L.; Delahunt, E.; Serner, A. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The Doha agreement classification is used to classify groin pain in athletes. We evaluated the inter-examiner reliability of this classification system. We prospectively recruited 48 male athletes (66 symptomatic sides) with groin pain between 10-2017 and 03-2020 at a sports medicine hospital in Qatar. Two examiners (23 and 10 years of clinical experience) performed history taking, and a standardized clinical examination blinded to each other's findings. Examiners classified groin pain using the Doha agreement terminology (adductor-, inguinal-, iliopsoas-, pubic-, hip-related groin pain, or other causes of groin pain). Multiple entities were ranked in order of perceived clinical importance. Each side was classified separately for bilateral groin pain. Inter-examiner reliability was calculated using Cohen's Kappa statistic (k). Inter-examiner reliability was slight to moderate for adductor- (k = 0.40), inguinal- (k = 0.44), iliopsoas- (k = 0.57), and pubic-related groin pain (k = 0.12), substantial for hip-related groin pain (k = 0.62), and slight for "other causes of groin pain" (k = 0.13). Ranking entities in order of perceived clinical importance improved inter-examiner reliability for adductor-, inguinal-, and iliopsoas-related groin pain (k = 0.52-0.65), but not for pubic (k = 0.12), hip (k = 0.51), and "other causes of groin pain" (k = 0.03). For participants with unilateral groin pain classified with a single entity (n = 7), there was 100% agreement between the two examiners. Inter-examiner reliability of the Doha agreement meeting classification system varied from slight to substantial, depending on the clinical entity. Agreement between examiners was perfect when athletes were classified with a single clinical entity of groin pain, but lower when athletes were classified with multiple clinical entities.